PENYELESAIAN SENGKETA WAKAF DI PENGADILAN AGAMA - Upi Komariah (Jurnal Hukum dan Peradilan, 2014)
Waqf is a legal act wakif to separate and / or give up some of their wealth either permanently or for a specified period in accordance with its importance for religious purposes and / or general welfare according to sharia. (Article 1, paragraph 1 of Law No. 41 of 2004 on Waqf). Religious Court duty and authority to examine, decide, and resolve the matter in the first instance between people who are Muslims in the field; a). marriage; b). inheritance; c). wills; d). grants; e). endowments; f). zakat; g). infaq; h). Sadaqah; and i). Shariah economy. (Article 49 paragraph (1) of Law No. 7 of 1989 as amended by Act No. 3 of 2006 on the Religious Courts). In the event of a dispute endowments, the remedies are done first is through the efforts of deliberation, new if done then of deliberation not come to fruition, the solution sought by the Religious Courts Keywords: Dispute, Waqf, Islamic Court